Molecular classification of glioblastoma based on immunohistochemical expression of EGFR, PDGFRA, NF1, IDH1, p53 and PTEN proteins - Jankowska, Sylwia; Lewandowska, Magdalena; Masztalewicz, Marta; Sagan, Leszek; Nowacki, Przemysław; Urasińska, Elżbieta (Polish Journal of Pathology, 2021)
Glioblastoma (GBM) is the most common and most aggressive primary tumor of the central nervous system. Current GBM treatments have low effectiveness. This is mainly due to the high degree of heterogeneity of GBM tumors. Despite similarities in the classic microscopic image, these tumors differ significantly in molecular terms. The aim of the study was to classify GBM tumors into one of four molecular types based on the immunohistochemical expression of EGFR, PDGFRA, NF1, IDH1, p53 and PTEN proteins and find the association between individual glioma molecular types and prognostic clinical and morphological parameters. From the group of 162 patients the classical molecular type of tumor was observed in 17 (10%) patients, in 23 (14%) the tumor was mesenchymal, in 32 (20%) proneural, and in 90 (56%) neural. No significant relationship was observed between the molecular type of GBM tumors and the studied clinical and morphological parameters of prognostic significance. There were also no statistically significant correlations between the GBM tumor molecular type and survival, both in terms of overall survival and relapse-free survival. Analyzing the impact of all prognostic variables and molecular type of GBM on the probability of overall survival, statistically significant relationships were found.